2004
DOI: 10.1111/j.1523-1755.2004.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

The renin-angiotensin system blockade does not prevent renal interstitial fibrosis induced by aristolochic acids

Abstract: Our data demonstrate that RAS modulation by salt depletion and pharmacologic blockade do not influence renal failure and interstitial fibrosis in the rat model of AAN. We suggest that pathways of interstitial renal fibrosis may be independent of RAS at least in some conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…At present, angiotensinconverting enzyme inhibitors and angiotensin II receptor type 1 blockers are clinically used to combat renal fibrosis (Locatelli et al, 2009;Morrow et al, 2010). However, these drugs are not able to completely stop the progression of renal fibrosis; in some conditions, such as aristolochic acid-induced renal fibrosis in rats, they are not effective at all (Debelle et al, 2004;Boor et al, 2007). Because renal fibrogenesis is a complex process that is involved in the activation of multiple cellular and molecular mediators, the incomplete antifibrotic effect of angiotensin-converting enzyme inhibitors and angiotensin II receptor type 1 blockers may be due to their limited targets.…”
Section: Introductionmentioning
confidence: 99%
“…At present, angiotensinconverting enzyme inhibitors and angiotensin II receptor type 1 blockers are clinically used to combat renal fibrosis (Locatelli et al, 2009;Morrow et al, 2010). However, these drugs are not able to completely stop the progression of renal fibrosis; in some conditions, such as aristolochic acid-induced renal fibrosis in rats, they are not effective at all (Debelle et al, 2004;Boor et al, 2007). Because renal fibrogenesis is a complex process that is involved in the activation of multiple cellular and molecular mediators, the incomplete antifibrotic effect of angiotensin-converting enzyme inhibitors and angiotensin II receptor type 1 blockers may be due to their limited targets.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, therapeutic strategies have been mainly conservative when renal insufficiency is detected [10] . Angiotensin-converting enzyme inhibitors did not modify the evolution of the renal disease [28] . Previous studies have investigated possible mechanisms of AA-induced nephrotoxicity both in vitro and in vivo and have suggested the role of AAI-induced apoptosis in renal tubular cells through either the endoplasmic reticulum (ER) stress pathway or the mitochondrial cell death pathway [29,30] .…”
Section: Discussionmentioning
confidence: 83%
“…13,14 There have been many hypothesizes about the pathogenesis of acute AAN. Some researchers found that there was blood vessel injury in AAN, 4,7,8,15 and they thought it could be one of the causes for the continuously progressing tubulointerstitial damage.…”
Section: Discussionmentioning
confidence: 99%